2002
DOI: 10.1007/s00421-002-0594-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chemosensitivity after intermittent hypoxic exposure does not affect exercise ventilation at sea level

Abstract: The purpose of the present study was to test the hypothesis that the ventilatory response to exercise at sea level may increase after intermittent hypoxic exposure for 1 week, accompanied by an increase in hypoxic or hypercapnic ventilatory chemosensitivity. One group of eight subjects (hypoxic group) were decompressed in a chamber to 432 torr (where 1 torr=1.0 mmHg, simulating an altitude of 4,500 m) over a period of 30 min and maintained at that pressure for 1 h daily for 7 days. Oxygen uptake and pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
5
15
1
Order By: Relevance
“…These investigations also show that the break in training for one or two days do not significantly affect the outcome of the IHT course. These conclusions were also expressed by Katayama et al [56,57], Koehle et al [58] and others. Later on, Katayama et al [59] conducted a study using the hypoxic tent, which was supported by 12.3% O 2 , one and 3 hours during the week.…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommesupporting
confidence: 60%
“…These investigations also show that the break in training for one or two days do not significantly affect the outcome of the IHT course. These conclusions were also expressed by Katayama et al [56,57], Koehle et al [58] and others. Later on, Katayama et al [59] conducted a study using the hypoxic tent, which was supported by 12.3% O 2 , one and 3 hours during the week.…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommesupporting
confidence: 60%
“…The relationship between hypoxic chemosensitivity and exercise _ V E following 7 days of intermittent hypoxia (1 h day À1 , 4,500 m) was recently examined (Katayama et al 2002). The authors reported no increase in exercise _ V E despite an increase in HVR.…”
Section: Discussionmentioning
confidence: 97%
“…The HVR increased after intermittent hypoxia, but no change in submaximal exercise _ V E was found. The authors therefore concluded that changes in hypoxic chemosensitivity had little effect on exercise _ V E (Katayama et al 2002).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, IH increases chemoreceptor gain and increases exercise _ V E : Indeed, _ V E during submaximal exercise is elevated following 11 nights of simulated altitude (3,000 m) (Gore et al 2001). In contrast, others have failed to show any effect of IH on exercise hyperpnoea (Katayama et al 2002;Foster et al 2006). In the current study, there was no effect of IH on the ventilatory response to submaximal exercise.…”
Section: Main Findingsmentioning
confidence: 92%